"الإرث عند العرب قبل الإسلام دراسة في التاريخ الاجتماعي" Heritage in Arab Regions before Islam -Study of Social History - Abdullah bin Awaid Al-Otaibi (Journal of General Union of Arab Archaeologists, 2022)
(AR) تًمثل دراسات التاريخ الاجتماعي ومنها موضوع الدراسة (الإرث عند العرب قبل الإسلام)، جانباً مهماً من حياة الأمم والشعوب؛ ونظراً لاختلاف طريقة كسب العرب (البدو – الحضر) للأموال، اختلف نظام الإرث بينهم، بالرغم من اتفاقهم على توزيع الإرث وفق الأعراف والتقاليد القبلية إما للنسب أو السبب. ولرسوخ هذا العُرف القبلي نجد أن العمل به قد استمر بالرغم مما ألحقه من أضرار في حياة بعض فئات المجتمع العربي قبل الإسلام حتى السنة الثالثة من الهجرة النبوية، وتحديداً بعد غزوة أحد عندما نزلت آيات المواريث، حيث نجد أن الشرع الحكيم يذكر تفاصيل الميراث في القرآن الكريم، في حين كانت أغلب الأحكام الشرعية تُذكر في القرآن مجملة وتبينها السنة بالتفصيل. وبالتالي فإن هذه الدراسة سوف تخدم أحد أحداث السيرة النبوية، وما يتعلق بأموال خديجة بنت خويلد رضي الله عنها التي توفيت في السنة العاشرة من البعثة. وستعتمد هذه الدراسة على نصوص مختارة، سواءَ أكانت نقوشاً أو شعراً جاهلياً، أو ما تم ذكره في المصادر والمراجع العربية والمعربة والأجنبية. (EN) Studies of social history, including the subject of the study (Heritage in Arab regions before Islam), are an important aspect of the life of all peoples. Due to the different ways of earning money by Arabs (Bedouins - urban), the heritage distribution method differed among them, despite their agreement to distribute heritage according to the tribal customs and traditions, either in ancestry or effect. Concerning the consolidation of this tribal custom, we find that it continued despite its damages that inflicted on the life of some groups of Arab society before Islam until the third year of the Prophet's migration, specifically after the Battle of Uhud when the Quranic verses of heritage were revealed. We find that the Sharia mentions the details of heritage in the Holy Quran. Most of the Islamic Shariah provisions were generally mentioned in the Quran and clarified in detail in Sunnah. Therefore, this study will discuss an important point in the biography of the Prophet Muhammad related to the wealth of Khadija bint Khuwaylid, may Allah be pleased with her, who died in the tenth year of the Prophet's Messengership. This study will depend on selected texts, whether they were inscriptions or pre-Islamic poetry, or what was mentioned in Arabic, translated, and foreign sources and references.